Analysis of Needs Seen in “Finding Dory”: A Movie Directed by Andrew Stanton - Hilma, Melitia; Fitriana, Eka; Isnaini, Muhammad (Journal of English Education Forum (JEEF), 2025)
This study examines the character development of Dory in the animated film "Finding Dory," directed by Andrew Stanton, through the framework of Maslow's hierarchy of needs. The research aims to identify the various needs reflected in Dory's character and analyze how the fulfillment of these needs influences her growth throughout the narrative. Utilizing qualitative methods, the study analyzes key scenes and dialogues to illustrate Dory's physiological, safety, belongingness, self-esteem, and self-actualization needs. The findings reveal that while Dory's physiological needs are minimally depicted, her safety needs are evident as she navigates vulnerable situations. Her profound desire for belongingness and love drives her quest to reunite with her family, highlighting the importance of relationships in her character development. Additionally, the study illustrates how Dory's journey enhances her self-esteem and leads to self-actualization as she learns to embrace her identity and capabilities. This research underscores the significance of character education in understanding personal growth and emotional intelligence. The insights gained from Dory's character can serve as a valuable resource for educators and parents, emphasizing the role of films in facilitating discussions about character development and the fulfillment of human needs. The study concludes with suggestions for incorporating character education into curricula and further research opportunities in the field of film analysis and character studies.